ECONOMIC IMPACT OF MINING IN KAZAKHSTAN - Kizatov, Yeskendir (School of Mining and Geosciences, 2023)
Kazakhstan is a country that economically relies on the export, especially on the export of the products of mining. Review of recent publications has proven the claim above. That is why mining sector has a significant impact on national economics. The research of data from the report, ordered by Minisrty of Industry and Infrastructure Development of Kazakhstan has shown that generally sector of mining in Kazakhstan is growing, however the taxation system has significant drawbacks, that are restraining it from sustainable development. These drawbacks are needed to be worked on.
Keywords: Type of access: Restricted; mining; Kazakhstan; Economic impact